1982
DOI: 10.1128/iai.36.1.209-214.1982
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and distribution of the hemagglutinins produced by Vibrio cholerae

Abstract: Examination of the distribution of cell-associated and soluble hemagglutinins (HA) produced by Vibrio cholerae revealed the existence offour different HAs. A cell-associated mannose-sensitive HA (MSHA) was produced only by the El Tor biotype. This was evident with all El Tor strains examined. It appears to be responsible for the HA biotyping differentiation of El Tor from classical biotype V. cholerae. The MSHA had no apparent divalent ion requirement; it was inhibited by D-mannose and D-fructose; and it was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0
1

Year Published

1987
1987
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(78 citation statements)
references
References 18 publications
4
73
0
1
Order By: Relevance
“…Inhibition of pili-mediated cellular agglutination and surface adhesion by the hexose D-mannose has been reported, and has been used to characterize the initial steps in biofilm formation by Vibrio cholerae and E. coli (Bhattacharjee & Srivastava, 1978;Hanne & Finkelstein, 1982;Pratt & Kolter, 1998;Moorthy & Watnick, 2004). In order to test the molecular properties of the MSHA pili in S. oneidensis, we explored whether biofilms are sensitive to carbohydrate addition, and developed an assay to probe whether the stability of established biofilms is dependent on MSHA-mediated cellular adhesion.…”
Section: Msha-mediated Cellular Adhesionmentioning
confidence: 99%
“…Inhibition of pili-mediated cellular agglutination and surface adhesion by the hexose D-mannose has been reported, and has been used to characterize the initial steps in biofilm formation by Vibrio cholerae and E. coli (Bhattacharjee & Srivastava, 1978;Hanne & Finkelstein, 1982;Pratt & Kolter, 1998;Moorthy & Watnick, 2004). In order to test the molecular properties of the MSHA pili in S. oneidensis, we explored whether biofilms are sensitive to carbohydrate addition, and developed an assay to probe whether the stability of established biofilms is dependent on MSHA-mediated cellular adhesion.…”
Section: Msha-mediated Cellular Adhesionmentioning
confidence: 99%
“…cholerae is known to produce various hemagglutinins (lectins) [3][4][5][6]. These differ immunologically and biologically from cholera toxin, which is an enterotoxin produced by V. cholerae [7][8][9]. One of these lectins has been well characterized and shown to be a mannose-specific lectin [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…These differ immunologically and biologically from cholera toxin, which is an enterotoxin produced by V. cholerae [7][8][9]. One of these lectins has been well characterized and shown to be a mannose-specific lectin [7][8][9]. It is supposed to play important roles in attachment of V. cholerae to epithelial membranes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Haemagglutination is an easily observable manifestation of the adhesive properties of bacteria. Previous reports [10] have described mannose-sensitive haemagglutinin in V. cholerae 01 biotype el tor and suggested that it may mediate attachment to host epithelial cell surfaces. In the present study, D-mannose could inhibit the adhesion only weakly, suggesting that the microbial and host factors that govern the adhesion of vibrios are complex.…”
Section: Strainmentioning
confidence: 92%